Effects of temperature and salinity on oxygen consumption and ammonia excretion in different colour strains of the Manila clam, Ruditapes philippinarum. (25th July 2016) - Nie, Hongtao; Chen, Peng; Huo, Zhongming; Chen, Yun; Hou, Xiaolin; Yang, Feng; Yan, Xiwu
Abstract: The metabolic responses of different colour strains of Ruditapes philippinarum in terms of oxygen consumption and ammonia excretion to changes in temperature (15–35°C) and salinity (20–40) were investigated. In our range of temperatures (15–35°C), oxygen consumption rate (OCR) increases in cultivated strains (White and Zebra) in opposition to the effect in the wild strain which reach a maximum at 25°C. The highest Q 10 coefficients were 2.741 for zebra strain, 4.326 for white strain, and 1.944 for wild at temperatures of 25–30, 30–35 and 20–25°C respectively. In our range of salinity (20–40°C), OCRs of white strain and zebra strain firstly decreased to lowest level at 25 and 30, and then increased to highest level at 35 and 40 respectively. When the salinity is beyond 35, the OCR decreased and the turning point was found in the white strain and wild, but the zebra strain OCR still increased to a highest level (1.906 mg g −1  h −1 ) at 40 ( P  <   0.05). These results show that the cultivated colour strains of R. philippinarum were different from wild in terms of metabolic responses, and information on its response to different temperature and salinity have implications in the aquaculture industry.